Ali Muhammad Ash-Shallabi's Thoughts About the Position of Women - Muhammad Sabri (AL-MAIYYAH : Media Transformasi Gender dalam Paradigma Sosial Keagamaan, 2024)
This article aims to explore Ali Muhammad Ash-Shallabi’s thoughts on understanding the position of women in the domestic sphere, public sphere, and typology in understanding the postulates of women. The research method used is descriptive-analytical. It involves describing the construction of Muhammad Ash-Shallabi's thoughts and critically analyzing them to identify the roots of his thought construction. Additionally, it examines the strengths and weaknesses of other figures. The author's primary data is the "Modern Islamic State" source, while their secondary data consists of articles, books, websites, and other scientific works on Ali Muhammad Ash-Shallabi by other individuals. The steps in this research are determining figures, inventorying data and selecting, then the data is analyzed critically, and a conclusion is drawn which will answer the problem formulation. The research results show that women’s position in the household is glorified, given education, and given their rights to defend themselves. The implication is, in the social realm, women must be careful in their relationships, but their rights are the same as men, both in education and so on. Apart from that, Ash-Shallabi’s typology is a semi-modernist.